2013
DOI: 10.1371/journal.pone.0075179
|View full text |Cite
|
Sign up to set email alerts
|

Residential Mercury Contamination in Adobe Brick Homes in Huancavelica, Peru

Abstract: This is the first study of adobe brick contamination anywhere in the world. Huancavelica, Peru is the site of historic cinnabar refining and one of the most mercury (Hg) contaminated urban areas in the world. Over 80% of homes in Huancavelica are constructed with adobe bricks made from Hg contaminated soil. In this study we measured total Hg concentrations in adobe brick, dirt floor, surface dust, and air samples from the interior of 60 adobe brick houses located in four neighborhoods. Concentrations of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…1 ). In some exceptional cases, exposure to inorganic Hg from soil or vapors may pose a direct health risk (Robins et al 2012 ; Hagan et al 2013 , 2015 ). Nevertheless, most industrially polluted sites raise concerns because of MeHg bioaccumulation, mobilization of Hg to downstream locations, and/or evasion of Hg to the atmosphere.…”
Section: Industrial Point Sources and Remediationmentioning
confidence: 99%
“…1 ). In some exceptional cases, exposure to inorganic Hg from soil or vapors may pose a direct health risk (Robins et al 2012 ; Hagan et al 2013 , 2015 ). Nevertheless, most industrially polluted sites raise concerns because of MeHg bioaccumulation, mobilization of Hg to downstream locations, and/or evasion of Hg to the atmosphere.…”
Section: Industrial Point Sources and Remediationmentioning
confidence: 99%
“…For example, a study of 100 homes located near smelting activities in southwest China reported a median Hg concentration of 1.8 mg/kg [40]. Other studies of homes in Hg mining and smelting areas reported Hg concentrations in house dust ranging from 6.4 to 120 mg/kg (median 20.9 mg/kg; n = 16) in Idrija, Slovenia [41] and 3.06 to 926 mg/kg (median 63.3 mg/kg; n = 60) in Huancavelica, Peru [42].…”
Section: Total Hg and Tc In Certified Reference Materials And Chds Sa...mentioning
confidence: 91%
“…Así pues, al igual que en el caso ecuatoriano, es difícil vincular directamente los malestares auto reportados por la población achuar con la exposición a metales pesados y metaloides. En poblaciones afectadas por diversas enfermedades que tienen que ver con sus condiciones de vida, una alta prevalencia de enfermedades tropicales y limitado acceso a servicios de salud, no sólo aumenta la vulnerabilidad de la población frente a la exposición a metales pesados y metaloides (38) si no que hace difícil determinar los efectos de exposiciones que pueden tener efectos inespecíficos. En el caso de la exposición al mercurio en población dedicada a la minería artesanal en Madre de Dios, Yard y colaboradores (34) miden los niveles de dicho metal en la población, mas no identifican las fuentes de exposición al mismo.…”
Section: Finalmente La Revisión Sistemática Realizada Por Intrinsik Environmental Sciencesunclassified
“…Estructura alimenticia y patrones de alimentación, preparación y consumo de alimentos En relación al consumo de pescado, una de las principales fuentes de proteína animal de la dieta indígena. Passos (38) concluye que, aunque existen muy pocos estudios sobre el tema, para la mayoría ésta es la principal fuente de exposición a mercurio. Su consumo ayuda a explicar incluso las variaciones en los resultados encontrados de acuerdo con la cantidad consumida durante un mismo periodo de tiempo (51)(52)(53)(54)(55)(56)(57) .…”
Section: Fuentes De Aguaunclassified